Sustainable Synthesis of Novel Green-Based Nanoparticles for Therapeutic Interventions and Environmental Remediation - Singh S.; Tiwari H.; Verma A.; Gupta P.; Chattopadhaya A.; Singh A.; Singh S.; Kumar B.; Mandal A.; Kumar R.; Yadav A.K.; Gautam H.K.; Gautam V. (My University, 2025)
The advancement in nanotechnology has completely revolutionized various fields, including pharmaceutical sciences, and streamlined the potential therapeutic of many diseases that endanger human life. The synthesis of green nanoparticles by biological processes is an aspect of the newly emerging scientific field known as “green nanotechnology”. Due to their safe, eco-friendly, nontoxic nature, green synthesis tools are better suited to produce nanoparticles between 1 and 100 nm. Nanoformulation of different types of nanoparticles has been made possible by using green production techniques and commercially feasible novel precursors, such as seed extracts, algae, and fungi, that act as potent reducing, capping, and stabilizing agents. In addition to this, the biofunctionalization of nanoparticles has also broadened its horizon in the field of environmental remediation and various novel therapeutic innovations including wound healing, antimicrobial, anticancer, and nano biosensing. However, the major challenge pertaining to green nanotechnology is the agglomeration of nanoparticles that may alter the surface topology, which can affect biological physiology, thereby contributing to system toxicity. Therefore, a thorough grasp of nanoparticle toxicity and biocompatibility is required to harness the applications of nanotechnology in therapeutics. © 2024 American Chemical Society